Music major, affects, and positive music listening experience. (July 2021) - Chang, Joanne; Lin, Peter; Hoffman, Edward
The use of music in mood regulation has gained increasing attention in recent years. In this study, 199 college students (70 music majors, 126 non-music majors; 101 males, 94 females) responded to two measures: the Positive and Negative Affect Schedule (PANAS) and a 15-item Positive Music Listening Experience Scale we developed (Cronbach's alpha = .90). It comprised 1 item on frequency of deliberate listening to music and 14 items concerning the effects of such listening on coping, solitude, and contemplative experience, comprising three subscales, respectively. Music majors scored significantly higher than non-music majors on overall Positive Music Listening Experience, as well as significantly higher in positive affect and lower in negative affect than non-music majors. Music majors scored significantly higher than non-music majors on the contemplation subscale; there were no significant differences on the coping and solitude subscales. In addition, the overall Positive Music Listening Experience score was linked significantly with positive affect and self-reported emotional intensity after the demographics were controlled. Contrary to our expectation, negative affect was not a significant predictor and was unrelated to all items of positive music listening experience. In contrast, positive affect was associated significantly with most items relating to positive music listening experience, particularly contemplative subscales items. We discuss the implications of these findings for better understanding the role of affect in influencing the effects of deliberate music listening.